2006
DOI: 10.1088/0953-4075/39/9/007
|View full text |Cite
|
Sign up to set email alerts
|

Fully differential cross sections for C6+single ionization of helium: the role of nucleus–nucleus interaction

Abstract: In this work, we present fully differential cross section (FDCS) calculations using distorted wave theories for helium single ionization by 2 MeV amu−1 C6+ ions. We study the influence of internuclear interaction on low-energy electron emission in the scattering plane. It is shown that by incorporating an internuclear effective charge which depends on the collision momentum transfer and taking into account its interplay with passive electron screening we obtain better agreement with experiments in most cases u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 29 publications
5
32
0
Order By: Relevance
“…where ν = Z P Z T /v is a Sommerfeld parameter, and Z T is the asymptotic charge of the target ion T . Using the two-dimensional Fourier transforms, the corresponding probability amplitudes in the momentumspace can be obtained as [19,42]…”
Section: Theorymentioning
confidence: 99%
“…where ν = Z P Z T /v is a Sommerfeld parameter, and Z T is the asymptotic charge of the target ion T . Using the two-dimensional Fourier transforms, the corresponding probability amplitudes in the momentumspace can be obtained as [19,42]…”
Section: Theorymentioning
confidence: 99%
“…The theoretical work that was carried out on the C 6+ and Au 24+/53+ systems has been dominated by the continuum distorted-wave eikonal-initial-state approximation (CDW-EIS) [1][2][3][4][5][6][7][8][9][10][11]18,21,23,25,27,[30][31][32][33]35,39,40], its earlier CDW incarnation [11,14,16,17,22,37], or related approximations [19,21,26,27,39,41], and by the classical trajectory Monte Carlo method (CTMC) [7,10,[12][13][14][15][16]19,[35][36][37][38]. Clearly, therefore, there is scope for a fresh approach.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, within the CDW-EIS scheme, it is possible to incorporate the interaction between the heavy nuclei, also known as N-N interaction, in a semiclassical way [26]. It has been shown that this approach is able to reproduce with reasonable agreement fully differential cross sections (FDCS) for single ionization of helium by heavy ions in a broad range of projectile velocities (see, e.g., [27][28][29][30]). …”
Section: Introductionmentioning
confidence: 99%